A Journey toward Self-knowledge in Patrick Modiano’s Novel Voyage de Noces - Bikulčius, Vytautas (Literatūra, 2021)
In this paper, based of a geocritical approach, a journey as some path leading toward self-knowledge in the novel of Patrick Modiano, French writer and Nobel Prize winner, Voyage de noces (1990), has been analyzed. A journey is understood as a path that leads toward self-knowledge because the characters of the novel undergo changes depending on the place they find themselves in. This journey gains several forms: it can simply be a journey from one point to another, also can have the aspect of escapism and finally be understood as deportation. In all these cases the nature of the journey changes depending on how the characters perceive themselves. The narrator admits that his aim is to write the autobiography of Ingrida, the character of the novel. Thus he sets out on a journey through her inner world, that naturally will last longer than the one from one point to another. The places are generally depicted as central and peripheral, the capital of the country and its outskirts or the capital and the regions of the country. The narrator tries to understand changes in Ingrida’s life and her faith, at the same time changes in the author’s self-knowledge happen: he becomes a writer.